Factors lead to obesity among children in MRSM Merbok, Kedah / Adibah Abdul Rahim and Nurul Zulaikha Abdul Patah Hasan - Abdul Rahim, Adibah; Abdul Patah Hasan, Nurul Zulaikha (2019)
Overweight and obesity as the fifth leading risk for global death causes at least 2.8 million die each year. It was also reported that 65 per cent of the world’s population live in countries where this risk kills more people than underweight does. Over 340 million children and adolescents aged 5-19 were overweight or obese in 2016. Overweight and obesity are defined as abnormal or excessive fat accumulation that may impair health. Due to that, most people that suffering obesity are tend to have several of illness like diabetes. The study examines the factor lead to obesity among children in MRSM Merbok, Kedah. A cross sectional survey among the students in MRSM Merbok, Kedah was applied and used in this study. The numbers of questionnaire distributed are 225. However, only 170 questionnaires are usable. The data obtained were analysed and these following findings were found. The relationship of environmental influence, lifestyle and dietary pattern are found significant. However, family influence is found not significant.